Do conditional cash transfers (CCTs) raise educational attainment? An impact evaluation of Juntos in Peru - Anja Gaentzsch (Development Policy Review, 2020)
Motivation: Many evaluations show that conditional cash transfer (CCT) programmes raise school enrolment and attendance of children from low-income households. Less evidence exists on the impact on learning and cognitive skills formation. This article contributes by evaluating the impacts of the CCT Juntos in Peru on school progression and performance in standardized test scores. Purpose We investigate the overall impact of Juntos upon educational outcomes of beneficiary children. Specifically, we address two questions: does Juntos have an impact on school participation? Can programme participation be linked to impacts upon cognitive skills? Approach and methods We use a quasi-experimental design that combines kernel matching with difference-in-difference estimation. We rely on data from the Young Lives panel survey and focus on a sample of 3,130 children aged 6-18 years old. Findings The article reports three main findings: (a) Juntos increases the chances of school enrolment and finishing primary school among children aged 12 to 18 years; (b) there is a positive effect on the transition to secondary school among the same age group, which is, however, only weakly significant at the 10% level; and (c) there is no positive impact on test scores of maths and language development among primary or secondary school-aged children. Policy implications The traditional demand-side focus of CCTs risks neglecting supply factors related to service infrastructure and quality. The article suggests that policy-makers need to study the structural mechanisms behind educational inequalities and integrate CCTs with measures to enhance skills formation for targeted households.
Keywords: 300; conditional cash transfer; educational attainment; Peru; propensity score matching with difference-in-difference